The Effect of Gibberellin Concentration on Maintaining the Quality of Tomatoes (Solanum lycopersicum) During Storage - Rachel Breemer; Gysberth Pattiruhu (Tropical Small Island Agriculture Management, 2025)
Tomatoes are horticultural products with high economic value and wide consumer appeal; however, they are highly perishable and require appropriate postharvest handling. One approach to preserving tomato quality is the application of gibberellin. This study aimed to evaluate the effect of gibberellin concentration on tomato quality during storage, focusing on parameters such as weight loss, firmness, moisture content, vitamin C, and total acidity. A Completely Randomized Design (CRD) with two factors was applied: gibberellin concentration (5, 10, and 15 ppm) and storage duration (4, 8, 12, 16, and 20 days). The results revealed that the lowest gibberellin concentration (5 ppm) was the most effective in maintaining tomato quality over 20 days of storage, resulting in weight loss of 3.23%, firmness of 0.96 KgF, moisture content of 92.78%, vitamin C of 3.67%, and total acidity of 8.6%. These findings provide important insights for postharvest management strategies to preserve tomato quality and economic value.